The Effect of Nesfatin-1 Levels on Paroxysmal Supraventricular Tachycardia. (June 2013) - Celik, Ahmet; Gurger, Mehtap; Can, Çagdas; Balin, Mehmet; Gul, Evrim; Kobat, Mehmet Ali; Gumusay, Umut; Sahan, Mustafa; Bursalı, Kazım Burak; Celiker, İlyas; Aydin, Suna; Aydin, Suleyman
Background: Nesfatin-1 was originally identified as a neuropeptide of the hypothalamus, which is a key integration area of the brain, where numerous neuropeptides and transmitters are released to participate in the control of essential body functions. In the literature, there are no studies showing the relationship between the nesfatin-1 level and paroxysmal supraventricular tachycardia. We hypothesize that the circulating levels of nesfatin-1 may increase during supraventricular tachycardia, to engage the vagal stimulation to terminate by the inhibition of neuropeptide-Y, and may activate oxytocin and the corticotropin-releasing hormone. Materials and Methods: This study includes 120 cases (80 patients and 40 controls). Patients with paroxysmal supraventricular tachycardia were compared with the control group with regard to sex, nesfatin-1 level, comorbid diseases, serum renal function values, and patients' vital findings. Results: The nesfatin-1 levels were significantly higher in the paroxysmal supraventricular tachycardia group than in the control group and positively correlated highly with heart rate ( r = 0.634; P < 0.001). The area under the receiver operating characteristic curve was 0.644 for the nesfatin-1 levels ( P = 0.0051). The sensitivity and specificity values of the nesfatin-1 levels were 41.2% and 95%, respectively (cutoff value >1743.7 pg/mL). Conclusion: At the end of this study, a statistically significant correlation was found between the serum nesfatin-1 level and supraventricular tachycardia. Although multifactorial causes may explain the relationship, we based our hypothesis on the relationship of the antagonistic effects of nesfatin-1 on the neuropeptide-Y and activated oxytocin.